EKSPLORASI FAKTOR PENENTU KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI YOGYAKARTA - Rahmawati Hanny Yustrianthe (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2024)
This study aims to examine the influence of tax understanding, tax awareness, and tax sanctions on the compliance of individual taxpayers in the Special Region of Yogyakarta. A sample of 100 respondents was selected using convenience sampling. The hypothesis testing technique employed is multiple linear regression. The results of this study indicate that only tax sanctions have an effect on the compliance of individual taxpayers in the Special Region of Yogyakarta, while tax understanding and tax awareness do not influence taxpayer compliance. This research provides implications not only for policymakers concerning taxpayer compliance but also for the development of tax accounting literature and behavioral accounting